STUDI MORFOMETRIK LEBAH TUKANG KAYU Xylocopa confusa Linn. (Hymenoptera: Anthophoridae) PADA DUA KETINGGIAN DI SUMATERA BARAT - Dwiyono, Alan; Jasmi, Jasmi; safitri, Elza (STKIP PGRI Sumbar, 2014)
ABSTRACT Carpenter bee or Xylocopa Confusa is one type of bees that nest in dead wood and bamboo. Xylocopa have important role in the process of natural pollination for plants . Xylocopa Confusa including semi- social bees, because there is no evident division to work in the colony members. Measurement of morphological characteristics of the bee is very important for bee taxonomist expert to put a type of bee into a particular taxa. Therefore research has been done on the study Morphometrics Carpenter Bee or Xylocopa confusa Linn. (Hymenoptera: Anthophoridae) In Two Altitude in West Sumatra. This study was conducted in February 2014 using a descriptive survey method by way of direct collection Xylocopa confusa found at the study site, namely the highlands and lowlands. Then, the researcher measure performed in laboratories that morphological main body length, head, chest, wings and hind legs. For the results, the size of the morphological characters of male bees Xylocopa Confusa were significantly different on the basis of the antenna length, femur length, metatarsus length, metatarsus width, while highly significant in the total body length, head width, wide chest, thick chest, front wing length, wing length width rear wing and rear. Size morphological characteristics of female bees Xylocopa Confusa were significantly different at the total body length, head width, the width of the antenna, wide chest, thick chest, front wing length, the width of the front wing, rear wing length, the width of the rear wing, femur length, femur width, tibia length, the width of the tibia and metatarsus length.